1974
DOI: 10.1037/h0037072
|View full text |Cite
|
Sign up to set email alerts
|

Backward masking as a measure of attention in schizophrenia.

Abstract: Backward-masking functions for two schizophrenic groups were compared with the masking functions for two control groups (college students and nonschizophrenic psychiatric patients). Masking functions were obtained for both singleletter and eight-letter visual displays. The procedure involved a forced-choice letter recognition method analogous to signal detection methodology. Both schizophrenic groups produced longer masking functions, under all conditions, than the two control groups whose functions were highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
98
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 19 publications
9
98
1
Order By: Relevance
“…In some of the earliest studies of backward masking, it was also found that schizophrenia patients did not reach unmasked performance levels (e.g., Saccuzzo et al 1974). Braff and Saccuzzo (1985) attributed this poor performance to floor and ceiling effects.…”
Section: Separation Of Biological From Methodological Causes Of Backwmentioning
confidence: 99%
See 1 more Smart Citation
“…In some of the earliest studies of backward masking, it was also found that schizophrenia patients did not reach unmasked performance levels (e.g., Saccuzzo et al 1974). Braff and Saccuzzo (1985) attributed this poor performance to floor and ceiling effects.…”
Section: Separation Of Biological From Methodological Causes Of Backwmentioning
confidence: 99%
“…The presence of masking deficits over a broad range of ISIs (short [Green et al 1994a[Green et al , 1994b and long [Saccuzzo et al 1974[Saccuzzo et al , 1996) may be due to heterogeneity amongst patients, differences in testing paradigms or deficits involving multiple stages of visual processing (Green et al 1997;Michaels and Turvey 1979). Alternatively, the lack of temporal specificity may be due to more general attentional or motivational factors in schizophrenia patients.…”
mentioning
confidence: 99%
“…Perceptual deficits have become increasingly well documented in the visual system in schizophrenia [9-17,18•,19-21] and may contribute to higher level cognitive impairments and community outcome [12,[22][23][24]. An early report by Saccuzzo et al [25] of visual backward masking dysfunction in schizophrenia was particularly important not only because it indicated deficits in the earliest components of visual information processing [16,26,27], but also because it suggested dysfunction of a particular visual pathway -the psychophysically defined transient visual pathway [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Saccuzzo, Hirt, and Spencer (1974), for example, found that schizophrenics required about twice as long as normal and patient controls to evade the effects of the mask. This result, which has subsequently been replicated in other investigations, has been interpreted in terms of abnormally slow processing in schizophrenic individuals Brody, Saccuzzo, & Braff, 1980;Saccuzzo, Braff, & Sprock, 1982a;Saccuzzo & Miller, 1977).…”
mentioning
confidence: 99%